WIFIA: Now We Put It to Work. Issue 9 (1st September 2014) - Curtis, Tom
Abstract : You've probably heard the old adage that sooner or later, every good idea turns into work. For WIFIA, a great idea born at the AWWA Water Utility Council, that time has come. WIFIA ‐ the Water Infrastructure Finance Innovation Act ‐ is the first new federal water infrastructure finance tool created since the Drinking Water State Revolving Fund was developed in 1996. Given that AWWA conceived WIFIA, designed the legislative construct, built the coalition of groups that supported it, and led the multiyear legislative effort that saw it enacted, it couldn't have been more fitting that President Obama signed WIFIA into law during ACE14.